PENGARUH LOGO DESIGN LOGO BARU BUMD YANG BERBASISKAN KEARIFAN LOKAL TERHADAP CITRA PERUSAHAAN (Studi Kuantitatif Mengenai Perubahan Logo Baru pada PDAM Kota Bandung) - Aat Ruchiat Nugroho (Program Studi Ilmu Komunikasi FBIK Unissula, 2014)
The purpose of this study is to know what extent the new logotype identityappearance to the image of corporate in customers at Bandung. This study uses four freevariabels deal by using research independent variable as according to condition offorming effective logo, that is: of logo an unique, functional of logo, form of logo andability of logo in presenting product to company image PDAM Kota Bandung as it thedependent variables that is perception, cognition, motivation and behaviour.The result of research indicates that factor is logo an unique, functional factor oflogo, logo form factor and ability of logo presents company, in simultan influential tocompany image PDAM Kota Bandung that is 66.7%. But in testing influence parsially, thatall subvariabel to indicate be factor is logo an unique 8.1%, simply only functional 27.6%,Â logo form 19.4% and ability of logo present to company in customer 11.7% from all theseapprearance of new logo identity of PDAM Kota Bandung influential direct in signifikan to company image and positive.Â